ANALISIS BATAS KECEPATAN PADA JALAN LOKAL SEKUNDER - Venasius H. A. Plue; Don Gaspar Noesaku da Costa; Agustinus H. Pattiraja (Eternitas: Jurnal Teknik Sipil, 2022)
The San Juan Road is one of the vehicle routes to El Tari airport and the Navy Airfield (LANUDAL) which also connects the intersection to the Widya Mandira Catholic University (UNWIRA) campus area. On these roads, there is often a choice of speed that is not in accordance with the function of the road so that it can endanger road users. The spot speed model is used to determine the actual speed at the study site, where the 85th percentile speed is used to determine the maximum speed which is then used to analyze accident risk for traffic conditions and roadside friction in the study location. From the research results, it is known that the actual speed is 31.66 km/hour for motorcycles, 20.16 km/hour for light vehicles and 16.79 km/hour for heavy vehicles. Theoretically, the speed is in accordance with the local road function classification, which is less than 40 km/hour. The 85th percentile speed is 26 - 30 km/h. However, due to fluctuations in the flow of vehicles entering/exiting gateways during peak hours and the aggressive behavior of road users, it was noted that there were 9 conflicts in the medium category due to the choice of critical crossing gaps for motorcyclists. The recommended solution is the installation of speed limit signs and prioritizing movement at unsignalized intersection areas, and socializing travel safety.